2014
DOI: 10.1519/jsc.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Season Low-Volume High-Intensity Plyometric Training on Explosive Actions and Endurance of Young Soccer Players

Abstract: Integrating specific training methods to improve explosive actions and endurance in youth soccer is an essential part of players' development. This study investigated the efficiency of short-term vertical plyometric training program within soccer practice to improve both explosive actions and endurance in young soccer players. Seventy-six players were recruited and assigned either to a training group (TG; n = 38; 13.2 ± 1.8 years) or a control group (CG; n = 38; 13.2 ± 1.8 years) group. All players trained twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
115
3
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 36 publications
13
115
3
16
Order By: Relevance
“…This is of relevance to establish the best training procedures in order to reduce the KD. Our outcomes are in line with the result of other very recent studies (de Villarreal, Suarez-Arrones, Requena, Haff, & Ferrete, 2015;Ramírez-Campillo et al, 2014 that demonstrated that the application of different strength training programmes (jumps and sprints, and plyometric exercises adapted to the age of our player) can increase ball velocity values in young soccer players. Furthermore, this kind of training should be incorporated in the daily workout routines since we can improve, at the same time, two of the most important and determinant soccer skills: jumping (heading) and kicking.…”
Section: Discussionsupporting
confidence: 91%
“…This is of relevance to establish the best training procedures in order to reduce the KD. Our outcomes are in line with the result of other very recent studies (de Villarreal, Suarez-Arrones, Requena, Haff, & Ferrete, 2015;Ramírez-Campillo et al, 2014 that demonstrated that the application of different strength training programmes (jumps and sprints, and plyometric exercises adapted to the age of our player) can increase ball velocity values in young soccer players. Furthermore, this kind of training should be incorporated in the daily workout routines since we can improve, at the same time, two of the most important and determinant soccer skills: jumping (heading) and kicking.…”
Section: Discussionsupporting
confidence: 91%
“…Change was greater than for the control groups (Tables II and III). Using the same change of direction speed test (Ramírez-Campillo, Meylan, et al, 2014), or a similar duration change of direction speed test , after completion of an almost equal plyometric training intervention as in this study, we reported an improvement in change of direction speed performance in young soccer players. During plyometric training, soccer players performed exercises designed to induce short ground contact times and high reactive strength index, which predict change of direction speed performance (Young, James, & Montgomery, 2002).…”
Section: Discussionsupporting
confidence: 66%
“…In another study on the effect of a plyometrics training program, including half-squat and leg-curl exercises, the experimental group improved both 20 m performance and CMJ (De Hoyo et al, 2015). Also, a study on adolescents showed that both 20m performance and CMJ increased over a 7-week plyometrics training program combined with soccer practice (Ramírez-Campillo et al, 2014). Finally, in a research on the effect of a 16-week plyometrics training program, gains in 20 m and standing broad jump were observed (Söhnlein, Müller, & Stöggl, 2014).…”
Section: Discussionmentioning
confidence: 96%